Tracking the Euro - Koen, Vincent (OECD Economics Department Working Papers, 2001)
During the first two years of monetary union, the euro's weakness surprised most market participants. Explanations proliferated ranging from fundamentals such as differences in growth prospects to psychological factors such as herd behaviour, but no single story fully accounts for the observed exchange rate path. Based on an eclectic approach, this paper offers an empirical analysis showing that terms-of-trade and saving/investment behaviour seem to have driven the euro exchange rate over the medium and longer run. While such econometric estimates ought to be interpreted with due care, they do support the view that towards the end of 2000, the euro was significantly undervalued ...